In situ detection and mass spectrometry imaging of protein-related metabolites in Bombyx batryticatus before and after frying with wheat bran - Liu, Pai; Wang, Jie-Min; Guo, Hao-Chuan; Zhao, Meng-Wei; Song, Yong-Xing; Guo, Hui; Duan, Xu-Hong; Yan, Yu-Ping; Zheng, Yu-Guang (Frontiers in Plant Science, 2023)
As a Chinese medicine, Bombyx Batryticatus has been used for thousands of years to treat convulsions, epilepsy, cough, asthma, headaches and purpura. In order to improve the quality and efficacy of Bombyx Batryticatus after frying with wheat bran, various methods have been developed to understand the intrinsic mechanisms of processed Bombyx Batryticatus. A matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) was applied to compare the spatial distribution and mass characteristics of protein-related metabolites from raw Bombyx Batryticatus (RBB) and fried Bombyx Batryticatus (FBB). After optimization of the experimental conditions, 21 ions were initially detected from Bombyx Batryticatus, including amino acids and peptides. The OPLS-DA results clarified 15 differential markers that were localized and visualized on cross sections of RBB and FBB. This method allows the visual identification and prediction of Bombyx Batryticatus before and after frying with wheat bran, as well as the study of amino acid and peptide changes from the perspective of chemometric analysis, providing a new idea for studying processed Bombyx Batryticatus.